1978
DOI: 10.1079/bjn19780105
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of urea from the blood to the rumen of sheep

Abstract: I. The rate of transfer of plasma urea-nitrogen to rumen ammonia was measured by infusion of 16NH,C1 and [16N]urea into sheep given brome grass (Bromus inermis) or lucerne (Medicago sativa) pellets. Urea was infused into the rumen or abomasum of two sheep given brome grass in order to increase the concentration of rumen ammonia.2. From 6.2 to 9.8 g/d of plasma urea-N were transferred to the rumen of sheep given brome grass pellets and a measurement of 1.3 g nitrogen/d was obtained for a sheep given lucerne pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…There are many ways in which the total urea movement and the distribution of movement of urea to various sectors of the gut can vary. Relative permeability of the rumen wall has been suggested to vary (Engelhardt et al 1978), and it has been suggested that the entry of urea into the reticulorumen is enhanced when ruminal ammonia concentration is low (Houpt, 1970;Kennedy & Milligan, 1978). whereby virtually total reabsorption of plasma urea-derived NH, (carrying 15N label, if present) can occur, but the efficiency of use of 'deep digesta' NH, may be improved.…”
Section: Nitrogen Metabolism 81mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways in which the total urea movement and the distribution of movement of urea to various sectors of the gut can vary. Relative permeability of the rumen wall has been suggested to vary (Engelhardt et al 1978), and it has been suggested that the entry of urea into the reticulorumen is enhanced when ruminal ammonia concentration is low (Houpt, 1970;Kennedy & Milligan, 1978). whereby virtually total reabsorption of plasma urea-derived NH, (carrying 15N label, if present) can occur, but the efficiency of use of 'deep digesta' NH, may be improved.…”
Section: Nitrogen Metabolism 81mentioning
confidence: 99%
“…Intake and net gain in nitrogen (as non-ammonia-N) Kennedy & Milligan, 1978). However, the nature of the processes involved allows for significant departures from the ideal conditions of mixing (assumed to operate in isotope studies) and thus leads to uncertainty about the direct and indirect influences, particularly of the blood urea-N contribution, to rumen N metabolism.…”
mentioning
confidence: 99%
“…N transfer between the rumen NH,-N and blood urea-N pools were calculated using a two-pool model (Nolan et al 1976;Kennedy & Milligan 1978~). Transfer quotients were calculated from the enrichment ratio with 15N of the two pools of interest.…”
Section: N Calculationsmentioning
confidence: 99%
“…Although there is evidence that rumen NH3 concentration is an important factor in the regulation of urea entry into the rumen under practical feeding conditions (Varady, Boda, Bajo, Szanyiova & Tomas, 1973;Faichney, 1974;Harrop & Phillipson, 1974;Kennedy & Milligan, 1978, urea degradation has been shown to be influenced also by the addition of fermentable carbohydrate to the diet (Cocimano & Leng, 1967;Potthast, Rahman & Pfeffer, 1976;Engelhardt, Hinderer & Wipper, 1978;Kennedy, 1980), by perfusion of the digesta with CO2 (Thorlacious, Dobson & Sellars, 1971) or by increases in rumen butyric acid concentration (Hinderer & Engelhardt, 1976;Norton, Janes & Armstrong, 1982). Evidence is also accumulating that considerable movement of urea can 6&cur across the post-rumen digestive tract, particularly the small intestine (Varady, T4shenov, Boda, Fejes & Kosta, 1979;Egan et al 1986), and that the control of urea transfer at these sites is probably different from that in the rumen.…”
Section: Introductionmentioning
confidence: 99%